2006
DOI: 10.1037/0096-1523.32.2.380
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative change in the dynamics of motor learning.

Abstract: The experiments examined qualitative and quantitative changes in the dynamics of learning a novel motor skill (roller ball task) as a function of the manipulation of a control parameter (initial ball speed). The focus was on the relation between the rates of change in performance over practice time and the changing time scales of the evolving attractor dynamic. Results showed 3 different learning patterns to the changes in the dynamics as a function of practice that were mediated by the initial ball speed. Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
68
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 42 publications
6
68
0
Order By: Relevance
“…The tendency to average data in statistical analyses may have masked important individual differences in performance (Newell, Liu, & Mayer-Kress, 2001;Withagen & Chemero, 2009). In future research, it might be more illuminating to consider the gaze behaviors of athletes at an individual level of analysis in order to understand the complex interaction of perception, cognition, and action capabilities that each individual exploits during everyday behavior in complex environments (for comparable approaches in the movement and perceptual learning literature, see Liu, Mayer-Kress, & Newell, 2006;Withagen & van Mermeskerken, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The tendency to average data in statistical analyses may have masked important individual differences in performance (Newell, Liu, & Mayer-Kress, 2001;Withagen & Chemero, 2009). In future research, it might be more illuminating to consider the gaze behaviors of athletes at an individual level of analysis in order to understand the complex interaction of perception, cognition, and action capabilities that each individual exploits during everyday behavior in complex environments (for comparable approaches in the movement and perceptual learning literature, see Liu, Mayer-Kress, & Newell, 2006;Withagen & van Mermeskerken, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The motor learning literature indicates that practicing a task leads to faster, more accurate, and less variable performance ͑Hatze, 1986; Liu et al, 2006;Schulz et al, 2000;Sosnik et al, 2004͒. Thus, similar developmental patterns for speech durations and variability ͑Eguchi and Hirsh, 1969; Kent, 1976͒ may simply result from children being less practiced speakers.…”
Section: Interpreting Variabilitymentioning
confidence: 99%
“…Deutsch and Newell ͑2004͒ observed that, with practice, some children approached adultlike values of force variability in a nonspeech ͑pinching͒ task and, moreover, that practice effects accounted for more variance than chronological age. Age effects can also be reduced by manipulating task demands, including accuracy requirements, force levels, and presence of feedback ͑Deutsch and Newell, 2001Newell, , 2003Newell, , 2004Yan et al, 2000͒. Finally, both speech and nonspeech studies indicate that production variability may increase during periods of learning or skill acquisition when the motor system is in transition to a new mode of organization ͑Berthier, 1996; Goffman et al, 2002;Liu et al, 2006;Thelen et al, 1996;von Hofsten, 1989͒. In this view, specific patterns of variability arise as individuals seek successful motoric strategies for a given goal ͑Jensen et al, 1995͒.…”
Section: Interpreting Variabilitymentioning
confidence: 99%
“…2 Young swimmers experience different rates of development that progress according to their own time scale. 3 For example, 2 structural-equation models reported that anthropometrics influence swimmers' kinematics and hence their performance. 4,5 The second topic of research interest is to model performance over time.…”
mentioning
confidence: 99%